Geographies of landscape: Representation, power and meaning - Carrabine, Eamonn (Theoretical criminology, 2018)
Green criminology has sought to blur the nature-culture binary and this article seeks to extend recent work by geographers writing on landscape to further our understanding of the shifting contours of the divide. The article begins by setting out these different approaches, before addressing how dynamics of surveillance and conquest are embedded in landscape photography. It then describes how the ways we visualize the Earth were reconfigured with the emergence of photography in the 19th century and how the world itself has been transformed into a target in our global media culture.